Madness is other people: alterity/ipseity and the sibling archetype. Issue 1 (13th April 2022) - Barcellos, Gustavo
Abstract: The issue of madness, always present in the hot‐tempered gods – Ares, Aphrodite, and Dionysus – has to do with what the ancient Greeks referred to as alterity. It was the Greeks who 'invented' this notion. What is otherness? It is, simply said, the extensive category of the Other. Let us examine a few aspects of the way this category is presented in mythical thinking in order to understand its place in psychology and madness. Alterity has to do with the Other, who is outside or inside me; ipseity is the possibility of remaining the same. This recognition has political, historical, ethical and, of course, psychological implications. And yet, it is archetypal, because that is where, as we will see, the issues of the sibling archetype fall. The sibling, as a primordial image in the soul, is present in the psychological evolution of each individual and each culture, and its influence inevitably projects itself into the history and construction of our connections with friends, companions, partners, associates, and colleagues – i.e. with all others, before confirmation is established in the soul that madness is other people. Abstract : Le sujet de la folie, toujours présent chez les dieux impétueux – Arès, Aphrodite, et Dionysos – est en lien avec ce que les Grecs anciens ont appelé l'altérité. Ce sont les Grecs qui ont « inventé » cette notion. Qu'est‐ce que l'altérité? Pour le dire simplement c'est la vaste catégorie de l'Autre. Examinons quelques aspects de la manière dont cette catégorie est montrée dans la pensée mythique, afin de comprendre sa place dans la psychologie et la folie. L'altérité a à voir avec l'Autre, qui est à l'extérieur ou à l'intérieur de moi. L'ipséité est la possibilité de rester le même. Cette prise de conscience a des conséquences politiques, historiques, éthiques et bien sûr psychologiques. Et pourtant, il s'agit de quelque chose d'archétypal, parce que c'est là que, comme nous le verrons, les questions de l'archétype de la sœur ou du frère se présentent. La sœur/le frère est une image primordiale de l'âme, elle est présente dans l'évolution psychologique de chacun et dans chaque culture. Son influence se projette inévitablement sur l'histoire et la construction de nos liens avec les amis, les compagnons, les conjoints, les associés et les collègues, c'est à dire avec tous les autres, avant que s'établisse dans l'âme la confirmation que la folie c'est les autres. Abstract : Das Problem des Wahnsinns, das bei den heißblütigen Göttern – Ares, Aphrodite und Dionysos – immer präsent ist, hat mit dem zu tun, was die alten Griechen als Alterität bezeichneten. Es waren die Griechen, die diesen Begriff 'erfunden' haben. Was ist Andersartigkeit? Es ist, einfach gesagt, die umfangreiche Kategorie des Anderen. Lassen Sie uns einige Aspekte der Darstellung dieser Kategorie im mythischen Denken untersuchen, um ihren Platz in der Psychologie und im Wahnsinn zu verstehen. Alterität hat mit dem Anderen zu tun, der außerhalb oder in mir ist; Ipseität ist die Möglichkeit, gleich zu bleiben. Diese Erkenntnis hat politische, historische, ethische und natürlich psychologische Implikationen. Und doch ist sie archetypisch, denn hierhinein fallen, wie wir sehen werden, die Probleme des Geschwister‐Archetyps. Das Geschwisterkind als Urbild in der Seele ist in der psychologischen Evolution jedes Einzelnen und jeder Kultur präsent und sein Einfluß projiziert sich unweigerlich in die Geschichte und Konstruktion unserer Verbindungen zu Freunden, Weggefährten, Partnern, Mitarbeitern und Kollegen – d.h. zu allen anderen, bevor in der Seele bestätigt wird, daß der Wahnsinn andere Menschen sind. Abstract : La questione della follia, sempre presente negli dei irascibili ‐ Ares, Afrodite e Dioniso ‐ ha a che fare con ciò che gli antichi greci chiamavano alterità. Furono i greci ad 'inventare' questa nozione. Cosa è l'alterità? È, semplicemente detto, la categoria estensiva dell'Altro. Esaminiamo alcuni aspetti del modo in cui questa categoria è presentata nel pensiero mitologico per comprenderne il posto nella psicologia e nella follia. L'alterità ha a che fare con l'Altro, che è fuori o dentro di me; l'ipseità è la possibilità di rimanere uguali a se stessi. Questo riconoscimento ha implicazioni politiche, storiche, morali e, ovviamente, psicologiche. Ciononostante, è archetipico, perché è lì che, come vedremo, cadono i problemi dell'archetipo del fratello. Il fratello, come immagine primordiale nell'anima, è presente nell'evoluzione psicologica di ogni individuo ed ogni cultura, e la sua influenza si proietta inevitabilmente nella storia e nella costruzione delle nostre connessioni con amici, compagni, partner, collaboratori, e colleghi ‐ cioè con tutti gli altri, prima che si stabilisca nell'anima la conferma che la follia "è" gli altri. Abstract : Проблема безумия, всегда присутствующая у вспыльчивых богов ‐ Ареса, Афродиты и Диониса, ‐ связана с тем, что древние греки называли инаковостью. Это понятие «изобрели» греки. Что такое инаковость? Проще говоря, это обширная категория Другого. Давайте рассмотрим несколько аспектов того, как эта категория представлена в мифическом мышлении, чтобы понять ее место в психологии и безумии. Отличающееся, иное имеет отношение к Другому, который находится вне или внутри меня; индивидуальная идентичность ‐ это возможность остаться прежним. Это признание имеет политические, исторические, этические и, конечно же, психологические последствия. И все же это архетип, потому что именно здесь, как мы увидим, возникают проблемы архетипа сиблингов. Брат или сестра, как изначальный образ души, присутствует в психологической эволюции каждого человека и каждой культуры, и его влияние неизбежно проецируется на историю и построение наших связей с друзьями, товарищами, партнерами, единомышленниками и коллегами ‐ т.е. со всеми остальными, до того, как в душе установится подтверждение того, что безумие ‐ это другие люди. Abstract : El tema de la locura, siempre presente en los dioses y diosas temperamentales – Ares, Afrodita y Dionisos ‐ tiene que ver con lo que los griegos antiguos refieren como alteridad. Fueron los griegos quienes 'inventaron' esta noción. ¿Qué es la otredad? Es, dicho simplemente, la categoría extensiva de lo Otro. Examinamos algunos aspectos del modo en que esta categoría es presentada en el pensamiento mítico para poder comprender su lugar en la psicología y la locura. Alteridad tiene que ver con la Otredad, que está afuera o dentro mío; ipseidad es la posibilidad de permanecer lo mismo. Este reconocimiento tiene implicancias políticas, históricas, éticas y por supuesto, psicológicas. Y todavía, es arquetípica, porque es allí donde se encuentran las cuestiones vinculadas al arquetipo fraterno. El hermano, como imagen primordial en el alma, está presente en la evolución psicológica de cada individuo y de cada cultura, y su influencia inevitablemente se proyecta en la historia y construcción de nuestras conexiones con amigos, compañeras, parejas, asociados y colegas – i.e. con todos los otros, antes que en el alma se establezca la confirmación de que la locura es otra persona. Abstract : 疯狂是他人:他异性/自感和同胞原型 疯狂总是存在于火脾气的神身上——阿瑞斯, 阿弗洛狄忒和狄奥尼索斯——它总是与古希腊所说的他异性有关。正是古希腊人发明了这个概念。他者是什么?简单的说, 关于"他"的极端的类别。让我们检视这种类别在神话思维中的几个面向, 以便我们理解它在心理学及疯狂中的位置。他异性与他者有关, 他在我之外或在我之内；自感是保持一致的可能性。这一认知具有政治、历史、伦理和心理学的含义。同时, 它是原型性的, 因为我们会看到, 同胞原型正落入其中。同胞兄弟姐妹, 作为灵魂中与生俱来的意象, 在每个个体每个文化的心理进化中都会呈现, 它的影响毫无疑问会投射到历史和我们与所有他人的关系建构中, 这包括朋友、同事、伴侣、合作伙伴等等, 在我们于灵魂中建立对疯狂的确认之前, 疯狂处于他者之中。 Abstract : A questão da loucura, sempre presente nos deuses de temperamento quente ‐ Ares, Afrodite e Dionísio ‐ tem a ver com o que os gregos antigos chamavam de alteridade. Foram os gregos que "inventaram" essa noção. O que é alteridade? É, simplesmente dito, a extensa categoria do Outro. Examinemos alguns aspectos da forma como essa categoria é apresentada no pensamento mítico para entender seu lugar na psicologia e na loucura. Alteridade tem a ver com o Outro, que está fora ou dentro de mim; ipseidade é a possibilidade de permanecer o mesmo. Esse reconhecimento tem implicações políticas, históricas, éticas e, é claro, psicológicas. E, no entanto, é arquetípico, porque é aí que, como veremos, as questões do arquétipo irmão incidem. O irmão, como uma imagem primordial na alma, está presente na evolução psicológica de cada indivíduo e de cada cultura, e sua influência inevitavelmente se projeta na história e construção de nossas conexões com amigos, companheiros, parceiros, associados e colegas ‐ ou seja, com todos os outros, antes que a confirmação seja estabelecida na alma de que a loucura é outra pessoa.